Integrating Hadratussyaikh Hasyim Asy'ari's Moral Values in Contemporary Education: Addressing the Challenges of the Digital Age - Muh Barid Nizarudin Wajdi; Siti Marpuah; Yuli Marlina (Tribakti: Jurnal Pemikiran Keislaman, 2025)
This research explores the relevance and application of Hadratussyaikh KH. M. Hasyim Asy'ari's moral education philosophy addresses the modern challenges of globalization and digitalization. The problem of moral degradation among young people, exacerbated by these contemporary pressures, highlights the urgent need for character-based education. Using a qualitative research approach with document analysis as the primary method, this study examines the integration of moral and intellectual development in Hadratussyaikh’s teachings. Key findings reveal that his philosophy balances cognitive growth and ethical behavior, emphasizing the practical application of moral virtues. The results also show that his principles can be adapted for broader educational contexts, both religious and secular. This research contributes to the ongoing discussion on character education and provides a framework for future empirical studies to assess the practical implications of his teachings in modern education systems.